Closed linear stapling in total laryngectomy- personal preferences and checklists to optimize outcomes - Bipin T. Varghese; Ankit Vishwani (Oral Oncology Reports)
Use of linear staplers for pharyngeal closure after total laryngectomy is yet to gain its due acceptance among head and neck surgeons because of a lack of experience sharing among those already well versed in it. Presented here are some nuances and the checklist that would enhance the safety and results of closed stapling in a total laryngectomy for advanced endolaryngeal cancers comprising meticulous separation of the tumour-free pharynx, the uninvolved vascularity maintained thyroid gland and the infrahyoid muscles [1] from the tumour involved larynx based on an angiosome concept.